Modulation of human bone marrow mesenchymal stem cells (BMMSC) by nigella sativa and trigona honey: an in vitro study - Masniza Muhamad Lasim,; Nurul Farihah Samsudin,; Zetty Nadia Mohd Zain,; Hayati Abdul Rahman,; Nur Syahrina Rahim,; Asral Wirda Ahmad Asnawi,; Nur Fariha Mohd Manzor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Maintenance of bone marrow mesenchymal stem cells (BMMSC) numbers is crucial for tissue repair and regeneration since adult stem cells are often limited in number, expansion capacity and lifespan. It is believed that certain types of foods are beneficial in the preservation and stimulation of stem cells throughout life. Black seeds and stingless bee honey are among the widely investigated functional food with general health promoting benefit. We aim to explore the proliferative, anti-apoptosis and anti-senescence effect of Nigella sativa and Trigona honey on BMMSC. Cell proliferation was evaluated using MTT assay. We performed flow cytometric analysis to verify stem cell surface markers while quantitative PCR was done to measure the relative expression of target genes. Results showed favourable concentration dependent enhancement of cell proliferation by 1 to 10 ug/mL Nigella sativa and 0.097% to 0.195% Trigona honey. Observation on BMMSC’s morphology and surface markers expression revealed no alteration on BMMSC stemness properties. In addition, gene expression analysis supported that there was a significant (p<0.05) increase in proliferation related gene, β-Catenin, and lower expression of apoptotic- and senescence-related gene, BAX and p21, respectively. These preliminary findings suggest a promising effect of Nigella sativa and Trigona honey on stem cell proliferation.